(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
This article is the complex research devoted to the development of economical, politicaldiplomatic, cultural relations and cooperation in the sphere of human rights and democracy of Kazakhstan with the European Union at modern stage. The history of formation and broadening of Kazakhstan-European relations is shown; theoretical ground for “new stage” of bilateral relations is given. It was analyzed the fundamental document signed between RK and the EU “Partnership and Cooperation Agreement”, which the main directions of bilateral cooperation are considered. Also in article the EU programs, such as TASIS, ТEMPUS were discussed.